DAYAK-DAYAK KENDURI TRADITION AT THE DEATH EVENT IN BLANG POROH VILLAGE, LABUHANHAJI BARAT DISTRICT - Rizki Maulana; Abdul Manan; Ruhamah (Indonesian Journal of Islamic History and Culture, 2021)
This study aims to determine the history of the Dayak-dayak feast, the process of the Dayak feast, the meaning contained in the Dayak-dayak feast and the social impact of the Dayak-dayak feast. The research method used is a qualitative method and the research instruments are interviews and documentation. In addition, researchers also collect data from print and electronic media. While the data sources, the researchers took directly from the keuchik, traditional leaders, religious leaders and the community, especially women who were experts or were directly involved in the implementation of the Dayak-Dayak feast tradition. The data obtained were analyzed using descriptive methods by reducing the data, displaying the data and drawing conclusions in order to provide answers about the research objectives. Discussing the history of the Dayak-Dayak feast and the beginning of the tradition, the people of Blang Poroh Village do not know for sure about the answer, because this tradition has been passed down from generation to generation. The Dayak feast is held on the second day of the third night of the corpses in the graves, the process of cooking the Dayak begins after the midday prayer at around two o'clock, the people of Blang Poroh Village, especially their neighbors and sisters, come together to the funeral home to help the process of making Dayak cakes. The meaning contained in the Dayak feast is other than family alms intended for the deceased as well as the bed or mattress of the deceased in the grave. With the Dayak feast, they could have a high social impact on the community because they could gather and strengthen friendships.